Study Description of Collaboration between the Marantha Christian University Library and Indonesian Higher Education Library Forum (FPPTI) West Java Region in Activities to Improve the Quality of Librarians - Prijana; Eza Alya (Universitas Airlangga, 2023)
Libraries as non-profit institutions cannot stand alone. There needs to be collaborative activities so that they can have a positive impact on each other through various forms. This research aims to determine the activities as a form of collaboration carried out by the Maranatha Christian University Library with the Indonesian Higher Education Library Forum in the West Java region and its impact on librarians. This research uses a descriptive qualitative approach method by taking primary data sources through interviews and observations, as well as secondary data sources through literature studies. The data analysis used uses data reduction, data presentation, as well as verification and drawing conclusions. The results of the research show that collaboration between university libraries and university library forums can result in 1) collaborative workshop activities to improve the quality of librarians, where in this research the focus is on research data management and visual analysis of institutional repositories 2) the opening of information networks quickly and widely through membership college library forum. The benefits of collaboration have significantly provided positive results for both parties, both the Maranatha Christian University Library and the Indonesian Higher Education Library Forum in the West Java region. Keywords: Library Cooperation; University Libraries; Library Forums